Bangladeshi Anatomists Perception for Structuring the Embryology and Genetics Oral Exam of M Phil Anatomy Course - Nahar, Lutfun; Shamim, Khondker Manzare; Sultana, Rubina; Bepari, Muhammad Abdul Jalil (Bangladesh Journal of Anatomy, 2015)
Context: Embryology and Genetics is a compulsory paper in the Master of Philosophy (MPhil) course in Anatomy in Bangladesh. Assessment of the knowledge, skills and attitudes of the students is a key component of a curriculum that is an integral part of any course design. Proper implementation of the assessment exams based on organized documents like exam format or card can make the course meaningful. The purpose of this study was to develop an exam format for structuring the oral exam to be followed by the examiners of the Embryology and Genetics paper of the MPhil Anatomy course. Materials & Methods: The descriptive study having both qualitative and quantitative components was carried out from January 2004 to June 2005 in the Department of Anatomy, Bangabandhu Sheikh Mujib Medical University (BSMMU) Dhaka, Bangladesh. The questionnaire was distributed to all the postgraduate anatomists (sixty) all over the country excepting eleven who were participated in focus group discussion. Results: The exam format is an important tool for structuring the oral exam but from time to time it should be modified depending upon the needs and situation. DOI: http://dx.doi.org/10.3329/bja.v12i1.22616 Bangladesh Journal of Anatomy, January 2014, Vol. 12 No. 1 pp 30-34